The Effect of Using Mind Mapping Technique in Violin Training on the Cognitive, Psychomotor Skills and Attitudes of the Students - (:unkn) unknown (TURKISH EDUCATION ASSOC, 2018)
In this research, the attitudes of the students towards mind mapping used in violin lessons was determined, analyzing the effect of the use of the mind mapping technique in violin education lessons on the cognitive and psychomotor skills of the students. 20 violin students who study at Bursa Zeki Muren Fine Arts High School were enrolled to the research, using the Pretest-Posttest Control Group Experimental Design. The research employed Test of Cognitive Field Evaluation and Performance Rating Scale, and random experimental and control groups were established according to the pretest scores. The experimental practice phase of the study was designed as six weeks (12 hours of course) and was carried out with each student individually. The violin education lessons of the students in the experimental group were conducted with the mind mapping technique, while the violin education lessons of the students in the control group were conducted with the traditional methods. The cognitive and psychomotor skill scores of the groups were compared upon the posttest measurements performed following the experimental study. 2 months after the posttest measurements, the Test of Cognitive Field Evaluation was reapplied in order to determine the retention of the cognitive skill levels of the students. At the end of the study, the attitudes of the students in the experimental group towards the mind mapping technique were determined by means of the Attitude Scale towards the Mind Mapping Technique Used in Violin Lessons. In line with the findings of the research, it was concluded that the violin education lessons conducted with the mind mapping technique are effective on the development of the cognitive and psychomotor skills of the students, and mind mapping increases the retention of the theoretical knowledge learned in the violin education lessons. Nevertheless, it was determined that the students developed a positive attitude towards the use of the mind mapping technique in the violin education lessons.
Keywords: Music education; Instrument education; Violin education; Mind Map Technique; Cognitive skill; Psychomotor skill; Attitude; SCIENCE